GRANDPARENTS THAT TAKE CARE OF GRANCHILDREN: ANALYSIS OF THE CARE PROFILE AND INTENSITY - Bragato, Aline Guarato da Cunha; Garcia, Luan Augusto Alves; Camargo, Fernanda Carolina; Paula, Fabiana Fernandes Silva de; Malaquias, Bruna Sthephanie Sousa; Elias, Henrique Ciabotti; Santos, Álvaro da Silva (Cogitare Enfermagem, 2023)
Objective: to identify the profile and intensity of the care provided by grandparents to grandchildren. Method: a descriptive and cross-sectional study by means of systematized random sampling, with application of a semi-structured questionnaire and execution of descriptive exploratory analysis. It was conducted in 2019 in the municipality of Triângulo Mineiro - Brazil. Results: a total of 392 grandparents caring for grandchildren were interviewed, mostly women (87.5%), retired (67.3%), with incomplete Elementary School (52.8%), hypertensive (71.9%) and with vision problems (69.4%). The main reason for the caregiver role was the fact that the parents had to work, and intensity of the care provided to the grandchildren was high. Conclusion: it is considered that the care relationship between grandparents and grandchildren is an invisible aspect to the scientific production and in the structuring of health programs, despite its impacts on older adults’ health status. The study broadens their visibility, with the need to unveil this topic so that it is possible to integrate them and strengthen public and social policies, especially in the health sector, given that it is an emerging phenomenon.